P4_15 Home Comforts - Smith, Jason; Kerr, Tendayi; Adams, Nathan; Brewster, Nick (Physics Special Topics, 2011)
This paper considers modifications a conventional terrestrial toilet design may require in order to ensure a successful flush if it was placed on the surface of mars. It is found that the water tank must be located a factor of 2.6 times higher than it would be on earth to compensate for reduced gravity on the Martian surface.